SOSIALISASI STRATEGI PEMASARAN DALAM MENGEMBANGKAN PRODUK KEWIRAUSAHAAN DENGAN IMPLEMENTASI WORD OF MOUTH DI RW 08 SUNTER AGUNG - Achmad Fauzi; Koerniawan Hidajat (LPPM Universitas Bina Bangsa, 2024)
Word of Mouth (WoM) marketing has become a significant strategy for Micro, Small and Medium Enterprises (MSMEs) in increasing brand awareness, building trust and driving sales. In the context of MSMEs in the RW 08 Sunter Agung area, socialization is an effective method for implementing WoM marketing. This research aims to evaluate the impact of socialization on the understanding and implementation of WoM marketing strategies by MSME mothers in the region. Through a participatory and interactive approach, empathy, and exchange of ideas, socialization was held to provide an in-depth understanding of the concept, implementation, and evaluation of WoM marketing. The research results showed that the outreach activities were successful in increasing MSME mothers' understanding of WoM marketing strategies, with 70% of participants stating they were ready to implement these strategies in their businesses. The enthusiasm and active involvement of MSME mothers in socialization also contributed to the success of the program. Thus, participation in outreach activities is an important key in ensuring a good understanding and effective implementation of WoM marketing strategies. This research provides valuable insight into the importance of socialization in the context of WoM marketing for MSMEs, with practical implications for local business development